Assessment of knowledge, attitude, and practices of acute kidney injury incidence with co-administration of piperacillin/tazobactam and vancomycin among healthcare workers: A cross-sectional study - Haytham A. Wali; Mohammed A. Alabdulwahed; Ghaida Y. Al-Hussain; Meaid A. Alabbad; Lojain H. Al-Khalaf; Sarah S. Alhumaidi; Khalid Alhussain; Sufyan M. Alomair; Abdulaziz S. Almulhim (Elsevier, 2023)
Background: No studies have identified a link between acute kidney injury (AKI) incidence due to the co-administration of vancomycin and piperacillin/tazobactam (VPT) and healthcare providers' knowledge, attitudes, and practices. We aimed to (1) assess the knowledge, attitudes, and practices towards AKI due to VPT co-administration among healthcare providers in Saudi Arabia, and (2) examine the relationship between healthcare providers' knowledge and attitudes about AKI due to VPT co-administration and their practices. Methods: This cross-sectional study was conducted between February 2022 and April 2022. Healthcare providers, including physicians, pharmacists, and nurses, were included in the study population. The correlation coefficient assessed the relationship between knowledge, attitude, and practice. Spearman's rho was used as a test statistic. Results: Of the invited healthcare providers, 192 responded to the survey. A significant difference in knowledge was found among healthcare providers for two variables: the definition of AKI (p < 0.001) and appropriate management of AKI due to VPT (p = 0.002). Physicians were found to rely less on the most common causative organisms of infection to guide empirical antibiotic therapy (p < 0.001). In addition, physicians were less likely to switch piperacillin/tazobactam to cefepime or meropenem in combination with vancomycin with AKI incidence (p = 0.001). A positive attitude towards the perceived AKI risk with VPT was positively correlated with avoiding using VPT unless no alternatives were available (Rho = 0.336) and taking protective measures when using VPT (Rho = 0.461). Conclusion: Deviation has been observed in the knowledge, attitudes, and practices of AKI incidence with the co-administration of piperacillin/tazobactam and vancomycin among healthcare workers. Interventions at the organizational level are recommended to guide best practices.